2016
DOI: 10.1002/2015jd024676
|View full text |Cite
|
Sign up to set email alerts
|

Detecting significant decreasing trends of land surface soil moisture in eastern China during the past three decades (1979–2010)

Abstract: Understanding the historical trends and driving mechanism of China's soil moisture change is an important step in combating climate change. Using the time series satellite-derived Essential Climate Variable Soil Moisture (ECV_SM) product, we detected a significant decrease trend in land surface soil moisture in eastern China over a 32 year period . Theoretical sensitivity analysis suggested that soil moisture is regulated collectively by precipitation (P), potential evapotranspiration (PET), land surface condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 53 publications
(76 reference statements)
3
42
0
Order By: Relevance
“…The two-stage comparison showed an effect of interdecadal climatic fluctuation, which mitigated water limitation by increasing rainfall in the period (b) of 2000-2015, though it began at an extremely low level around 2000 [53]. As shown in previous research, over the last half-century, the annual mean temperature, precipitation, and relative humidity suggested a warming and drying trend in the Horqin Sandy Land [54]; over 1979-2010, the soil moisture of land surface was significantly decrease in the Liaohe Basin [55]; after 1997, a national "warming hiatus" and increase in "flash droughts" were observed in Northeastern China [56]. Thus, the trend of climate still involved uncertainties and gaps among increased rainfall, droughts, and vegetation enhancement in the HQA.…”
Section: Effect Of Climate Variables On Ndvimentioning
confidence: 93%
“…The two-stage comparison showed an effect of interdecadal climatic fluctuation, which mitigated water limitation by increasing rainfall in the period (b) of 2000-2015, though it began at an extremely low level around 2000 [53]. As shown in previous research, over the last half-century, the annual mean temperature, precipitation, and relative humidity suggested a warming and drying trend in the Horqin Sandy Land [54]; over 1979-2010, the soil moisture of land surface was significantly decrease in the Liaohe Basin [55]; after 1997, a national "warming hiatus" and increase in "flash droughts" were observed in Northeastern China [56]. Thus, the trend of climate still involved uncertainties and gaps among increased rainfall, droughts, and vegetation enhancement in the HQA.…”
Section: Effect Of Climate Variables On Ndvimentioning
confidence: 93%
“…Regional studies, such as those in China, India, and North America, indicated that ECV outperforms other soil moisture data sets (An et al, ; Chakravorty et al, ; Jia et al, ; Nicolai‐Shaw et al, ; Qiu et al, ; Zeng et al, ). In recent studies, ECV soil moisture has been widely accepted and used as reliable soil moisture observations for estimating long‐term changes of hydrological cycle in different regions (e.g., Chen et al, ; Feng, ; Feng & Zhang, ; Zohaib et al, ). Therefore, given the lack of a global‐scale high‐density network of in situ soil moisture measurements, as well as the large inconsistency of specifications of the existing in situ measurements (e.g., measurement methods, installation modes, and depths), this study employs ECV soil moisture as a reference to evaluate model‐based soil moisture data sets generated by different types of models (Dorigo et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Estimation of long‐term trends in soil moisture is one of the important scientific questions in climate change studies (e.g., Chen et al, ; Cheng et al, , ). Therefore, the long‐term trends estimated from different soil moisture data sets are compared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on satellite observations and model simulations, widespread soil moisture (SM) drying in the root zone layer (i.e., at depths of 0–100 cm) has been witnessed globally in past decades (e.g., Cheng et al, ; Cheng & Huang, ; Chen et al, ; Dai, ). Global‐scale SM drying has also been corroborated by meteorological drought indices, such as the Palmer Drought Severity Index (Dai et al, ), Standardized Precipitation Index (Hirschi et al, ; Wang et al, ; Zhang et al, ), and Aridity Index (Huang et al, ).…”
Section: Introductionmentioning
confidence: 99%